القدرات الوجدانية وأثرها في الحل الابتكاري لمشكلات العمل : دراسة استطلاعية في مستشفى ابن سينا التعليمي في الموصل - منال عبدالجبار السماك; امال سرحان سليمان الطائي; بسام منيب علي الطائي (PROSPECTIVE RESEARCHES, 2023)
The emotional abilities represent one of the main requirements of going along with the environment. It cannot respond to an actual performance without taking into account these abilities because they are linked in one way or another with how to reach innovative solutions to the problems. The research has aimed through the conceptual framework show to the emotional impact of capacity in the access to innovative solutions to the problems in the organization of health research sample. The researchers have sought to include these two variables in their research within the framework of a comprehensive theoretical analysis in an attempt to reach and affect relationship between them. Generally, the research tries to find the answer to the following questions: 1- Are the emotional abilities considered one of the control skills in the possibility of achieving excellence in organization of health research sample? 2- Do the managers in the organization under research have any idea about the impact of emotional capacity in the innovative solutions to the problems? 3- What is the role of emotional capacity in the innovative solutions to the problems of the organization of health? The results give a set of conclusions, which were the most prominent of the innovative solutions to problems in the organization researched. There is a significant effect of emotional capacity in the innovative solutions to problems in the organization under researched. Depending on the conclusion reached by the research a set of recommendations have been provided.